Solid waste management in Africa: A review - Bello, Ibrahim Adebayo; Ismail, Muhamad Norshafiq; Kabbashi, Nassereldeen Ahmed (OMICS International, 2016)
As a result of globalization, the quantity and generation rate of solid waste in Africa have increased tremendously and this calls for the need to salvage the situation before it gets out of hand. This article presents the review of solid waste trends in Africa from the pre-colonial era till the present day. It also discusses the composition of solid wastes, collection, transportation and disposal in different African countries. Different types of waste have been generated over the years but the management strategies implemented are inadequate. Waste management in African is faced with numerous challenges and recommendations for improved and efficient solid waste management have been proposed.